Analisis Kebutuhan Pengembangan E-LKPD Interaktif Bahasa Indonesia Berbasis Genre di Sekolah Dasar - Faidah, Ngainul; Usman, Herlina; Yarmi, Gusti (SAP (Susunan Artikel Pendidikan), 2024)
This study aims to describe the analysis of the development needs of genre-based Indonesian Electronic Student Worksheets. The result of this study is to determine the response of students and teachers to the development needs of E-LKPD Interactive Bahasa Indonesia. This study uses qualitative descriptive methods using instruments in the form of questionnaires and interviews to determine the needs of students and teachers in Indonesian learning. The development model in the development of student worksheets uses the ADDIE model which consists of 5 stages namely Analyze, Design, Develop, Implement and Evaluate. Needs analysis data was obtained from 30 students and 2 homeroom teachers. Based on the results of research that has been done, it can be concluded that Electronic Student Worksheets are Indonesian indispensable in learning, especially writing materials. This can be seen from the results of teacher interviews and student questionnaire results which show that there are still limited LKPD and teachers rarely use technology-based media when learning in class. Students sometimes get bored and have difficulty in expressing ideas / ideas through writing, so the ability to write various types of texts is still lacking, with an average class score of only 63. Based on the questionnaire, 80% of students agreed that interactive Electronic Worksheets were developed, and based on interviews, all teachers agreed to develop Indonesian genre based Interactive LKPD.